Applying the Diffusion of Innovation Theory to Address the Challenges of Implementing PSAK 55 in Rural Banks - Chairanisa Natasha Miraza; Cut Darmawati; Abdul Malik Fajri; Riantari Maharani; Aulia Khairullah (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2025)
This study aims to provide recommendations for addressing the challenges that arise in the implementation of PSAK 55 in Rural Banks (BPR). The research employs a descriptive qualitative approach using interview techniques, analyzed with NVivo12 Pro software through content analysis, thematic analysis, and constant comparative methods. The findings reveal several key obstacles, including limited human resource competence in calculating the fair value of collateral and estimating future cash flows, both of which are essential for determining CKPN (Allowance for Impairment Losses). These challenges are further exacerbated by doubts among many BPR practitioners regarding the effectiveness of PSAK 55 in reducing credit risk losses, as the standard has never been implemented in the BPR sector before. In response to these barriers, this study offers strategic recommendations based on the Diffusion of Innovation Theory, including enhanced dissemination of information about PSAK 55, strengthened collaboration among BPRs through peer support mechanisms—such as initiatives by BPRKU 3 to assist BPRKU 1 and 2 by providing CKPN calculation templates and technical training and active regulatory involvement in promoting broader acceptance of the standard. Accordingly, this research contributes conceptually by applying the Diffusion of Innovation Theory to explain the adoption process of PSAK 55 within the practical context of BPRs. It also provides practical contributions by offering actionable recommendations that can be used by professional associations to design training and outreach programs, and by BPRs to prepare internal strategies for more effective implementation of PSAK 55.